Digital transformation in the construction industry: Analysing the impact of technological changes on construction processes - Olena Emelianova; Viktoriya Tytok; Kateryna Lavrukhina; Inna Shatrova; Olena Demydova (ESTOA: Revista de la Facultad de Arquitectura y Urbanismo de la Universidad de Cuenca)
The relevance of the problem under study lies in the rapid development of digital technologies, which provide unique opportunities for optimising and improving the efficiency of construction production. The purpose of the study is to analyse the impact of digital changes on the technology and organisation of construction activities in Ukraine. The methods of literature review, experimentation, and abduction were used. The study determined which digital technologies, such as BIM, IoT, and AI, are most important to construction organisations. A framework of efficiency-boosting tactics, including personnel training, process optimisation, and technology integration, was created. To visualise data on digital priorities and initiatives, an application was developed. The study emphasised the significance of all-encompassing digital transformation plans and the demand for ongoing innovation in the building sector.